The Correlation Between Mean Pulmonary Arterial Pressure And NT-proBNP In Adult Patient With Uncorrected Atrial Septal Defect - Jomanzyah MUA., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
The Correlation Between Mean Pulmonary Arterial Pressure And NT-proBNP In AdultPatient With Uncorrected Atrial Septal Defect